Diffuse neonatal hemangiomatosis. A case report with limited visceral involvement. - Simonetti, V.; Legori, A.; Strippoli, D.; Motolese, A. (European Journal of Pediatric Dermatology, 2006)
Hemangiomas represent a relatively common clinical entity in the pediatric age, affecting approximately 2% of newborns. 15-20% of these patients present a clear case of multiple hemangiomatosis. The newborns affected by multiple hemangiomatosis can have simply cutaneous involvement, emerging as a benign pattern known as benign neonatal hemangiomatosis, or have a cutaneous and visceral involvement, characteristic of diffuse or disseminated neonatal hemangiomatosis. This rare form of hemangiomatosis presents a serious prognosis, often fatal due to associated visceral complications and necessitates early and timely treatment. Here we describe the case of a baby affected by multiple hemangiomatosis with limited cutaneous and visceral involvement, successfully treated with high dose steroids.